2021
DOI: 10.1002/adma.202104450
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework Photonic Balls: Single Object Analysis for Local Thermal Probing

Abstract: Due to their high porosity and chemical versatility, metal–organic frameworks (MOFs) exhibit physical properties appealing for photonic‐based applications. While several MOF photonic structures have been reported, examples of applications thereof are mainly limited to chemical sensing. Herein, the range of application of photonic MOFs is extended to local thermal and photothermal sensing by integrating them into a new architecture: MOF photonic balls. Micrometric‐sized photonic balls are made of monodispersed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 94 publications
(117 reference statements)
0
36
0
Order By: Relevance
“…As a comparison, this value is two and three orders of magnitude higher than the temperature‐induced refractive index variation of poly(methyl methacrylate), and dense TiO 2 respectively [ 50 ] over a similar temperature range. [ 51 ] The thermal sensitivity of the porous crack‐patterned gratings is of the same order of magnitude of ZIF‐8 photonic balls in presence of EtOH vapors. [ 50 ] Notably, as shown in Figure 6d, the n / T curves at lower IPA P / P 0 (75%, 50%, and 25%) present the same sensitivity but are displaced toward lower temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…As a comparison, this value is two and three orders of magnitude higher than the temperature‐induced refractive index variation of poly(methyl methacrylate), and dense TiO 2 respectively [ 50 ] over a similar temperature range. [ 51 ] The thermal sensitivity of the porous crack‐patterned gratings is of the same order of magnitude of ZIF‐8 photonic balls in presence of EtOH vapors. [ 50 ] Notably, as shown in Figure 6d, the n / T curves at lower IPA P / P 0 (75%, 50%, and 25%) present the same sensitivity but are displaced toward lower temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…8d, M. Faustini et al 113 demonstrated the fabrication of MOF photonic spheres with amorphous photonic structures via a spray-drying approach, which was inexpensive with high throughput. This method for the preparation of MOF photonic balls shows versatility, which has great promise in the application of chemical sensing.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…Spray dry could confine the colloidal particles in droplets. During evaporation, the particles could be squeezed through the shrinkage of the droplet size ( Figure 7a ) [ 138 ]. The polyhedra were assembled into balls, which could be used for measuring the temperature.…”
Section: Reviewmentioning
confidence: 99%
“… a) Schematic illustration of the self-assembly of ZIF-8 particles via spray drying. Figure 7a was reproduced from [ 138 ], C. Avci et al, “Metal-Organic Framework Photonic Balls: Single Object Analysis for Local Thermal Probing”, Advanced Materials, with permission from John Wiley and Sons. Copyright © 2021 WILEY‐VCH GmbH.…”
Section: Reviewmentioning
confidence: 99%